Bibliometric Analysis of Carbon Footprint Studies Within the Scope of Sustainability - Rukiye Sefanur Altay; Asude Ateş; Hülya Demirel (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2025)
Today, the world climate is undergoing negative changes as a result of the unconscious use of resources, increasing energy demand and anthropogenic effects resulting from the development of industry. Climate changes occurring on a global scale are long-term and bring with them many irreversible consequences. Various improvement activities are based on sustainability in the fight against global climate change. To ensure environmental sustainability, practices are carried out in industrial areas to determine carbon footprints and reduce carbon emissions accordingly. One of the important steps taken in this context is the European Green Deal action plan, which is the roadmap for the green transformation required by the Paris Climate Agreement of the EU, to which Turkey is also a party. The European Green Deal aims to make Europe the first carbon-neutral continent in 2050 and to bring carbon emissions in the atmosphere back to pre-industrial revolution levels. In line with this goal, activities aimed at carbon footprint studies have gained serious momentum. This study aims to determine the current status of carbon footprint studies on a global scale, their progress and their distribution on a country basis through bibliometric analysis. Bibliometric analysis is a social network analysis that guides researchers regarding the interactions of existing studies and future studies. 1305 indexed journal articles published between 2020 and 2024 were downloaded via the Web of Science database and analyzed. Network maps and graphs showed correlations between keywords, countries, and journals. Researchers in China and America have made significant contributions to this field. It is seen that the studies examined serve sustainability development goals and that the studies mainly target climate action with 722 articles.